EXPERIMENTAL IRON DEFICIENCY ANEMIA: IRON NANOPARTICLES SUBSTANCE EFFECTS ON OOCYTES MEIOTIC MATURATION AND UTERINE CONTRACTILITY - Литвиненко, А.П.; Blashky, T.V.; Рєзніченко, Л.С.; Voznesenskaya, T.; Грузіна, Т.Г. (World of Medicine and Biology, 2015)
The effect of the introduction of the zero-valent iron nanoparticles substance (Fe0, nZVI) on the functional state of the reproductive system in experimental iron deficiency anemia in mice (IDA) has been studied. It was found that in the five-fold administration Fe0 leads to an improvement in the quality of oocytes and the normalization of the contractility of ovarian and cervical departments of the mouse uterus.